Evasión tributaria y la rentabilidad de los comerciantes de abarrotes del mercado N° 03 en el distrito de Tarapoto - año 2014. - Alarcón Jiménez, Khunji Marilyn (2014)
This research aims to determine the relationship of Tax Evasion and profitability Merchants Grocery Market N ° 03 in the District of Tarapoto - Year 2014. Deductive Method one going from the general to the particular was used. The deductive method is one that some generals accepted as papers valid data to deduce by logical reasoning, several assumptions, ie; of truths previously established general principles, and then apply to individual cases and thus verify its validity. This thesis uses the Experimental design; and to manipulate the independent variables for their effects on dependent variables in a control situation. The most relevant traders involved in this study groceries results is the informality of businesses that have been operating for merchants who have a relatively low educational level; most of these do not have taxation; Likewise businesses have less than S / daily sales. 800 and finally did not receive tax training. The results of our study reflect a Lower Profitability, as most relevant result of the investigation, it is the finding of a significant relationship between the Tax Evasion and profitability, the latter measured based on sales of businesses involved in this study; this allows us to test the research hypotheses, which inferred a direct relationship between the two variables. The most important factors that determine the tax evasion are informal, low level of instruction, with no constitution as a company, lack of taxation, low sales and lack of tax training; constituting a strong issue in business with tax evasion. Similarly it has been determined that the vast majority of these entrepreneurs do not declare their employees causing a failure in determining the contribution to Essalud. Agree with the author Tarrillo that the lack of adequate disclosure by the State concerning the taxes and the purpose thereof, brings the absence of a tax culture and consciousness, causing taxpayers are more likely to fall in tax evasion and avoidance.